Readiness for research data management in the life sciences at the University of the Witwatersrand - Potgieter, Salomé (Library and Information Studies Centre (LISC), 2023)
Because of the importance of Research Data Management (RDM) in the life sciences, where vast amounts of research data in different complex formats are being produced, this study aimed to assess the state of RDM readiness in the life sciences at Wits to ascertain what support is needed with regards to RDM. In order to achieve the aim, the current RDM practices and needs of researchers, as well as the challenges they face, were investigated. The Jisc Research Data Lifecycle (Jisc, 2021a) was used to guide the literature review, frame data collection, analyse data and advise on some of the main findings and recommendations. A mixed methods approach and an explanatory sequential design were used to achieve the research objectives. For the quantitative phase of research, an online questionnaire was used to collect data. As the total target population (282) was not big, a census was conducted. The questionnaire was administered using SurveyMonkey software. During the qualitative part of the research, semi-structured interviews were used to explain the quantitative results. Five participants were purposively sampled to take part in interviews. The statistical package, MS Excel, was used to analyse quantitative data whilst qualitative data were analysed by thematic analysis. The study showed that life sciences researchers at Wits have adopted many RDM practices, and researchers are increasingly becoming aware of the importance of the openness of data. However, they are dealing with similar RDM issues as their peers worldwide. Results highlighted challenges of, amongst others, the lack of an RDM policy as well as the lack of, or unawareness of, appropriate RDM training and support at Wits. As formal implementation of RDM still needs to take place at Wits, it is recommended that Wits puts an RDM policy in place, followed by suitable RDM infrastructure and awareness making of current services.